Determination of Thickness Uniformity of Nickel Coatings Deposited on Zirconium Alloy by Magnetron Sputtering; AIP Conference Proceedings; Vol. 1899 : Prospects of Fundamental Sciences Development (PFSD-2017) - Jingwen Qiao (Energy and power technologies in material science, 2017)
Title screen